Endoresection of choroidal melanoma using high-frequency electric welding of biological tissues (Ukrainian Journal of Ophthalmology, 2026)
Background: The evolution of ocular oncology over the recent decades has been characterized by the emphasis on organ saving approaches, the main method requirement being the greatest degree of radicalism of tumor resection with a minimum amount of damage to surrounding tissues.Purpose: To assess the efficacy of endoresection for uveal melanoma, with the high-frequency electric welding used for achievement of hemostasis.Materials and Methods: Twenty patients (21 eyes; age, 51.6 (12.43) years) with choroidal melanoma were under our observation during 2010 to 2014. Prior to any treatment, the maximum tumor thickness based on ultrasound examination (Cine Scan) was 5.4 (2.6) mm (range, 1.4 mm to 10 mm), with the mean largest basal tumor diameter of 10.8 (3.7) mm (range, 7.6 mm to 15.8 mm). Patients underwent strontium-90 brachytherapy plus transpupillary thermotherapy to devitalize the tumor. Two months to 3 years thereafter, they underwent a 20-G three-port vitrectomy during which endoresection of melanoma was performed.Results: In 19 eyes (90%), massive hemorrhage from uveal melanoma vessles and choroidal vessels was observed during excision of tumor tissue, and was successfully resolved with high-frequency electric welding using a unipolar endovitreal probe. All patients were still alive at the end of observation period of 2 to 6 years. Two of them underwent enucleation due to progressive tumor growth and due to subacute uveitis and phthisis bulbi, respectively.Conclusions: Endoresection is an alternative technique for the treatment of uveal melanoma, with the eye salvage rate as high as 90%. The use of high-frequency electric welding of biological tissues in endoresection of uveal melanoma allowed us to avoid choroidal and ciliary hemorrhage in all cases, thus reducing the risk of intra- and post-operative complication.
Keywords: меланома судинної оболонки; резекція; електрозварювання